Management of challenges with large cervical masses - Chugh, Mansi; Goel, Bharti; Sehgal, Alka; Aggarwal, Phiza (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Cervical adenomyomas are extremely rare benign tumors and are often overlooked as a differential diagnosis of large cervical masses. Herein, we report a case of a 23-year-old nulliparous woman with polypoid adenomyoma arising from the endocervix. The mass was filling up the vagina and stretching the anterior fornix up into the lower abdomen, hence the origin of the mass could not be identified on clinical examination or imaging. Therefore, management of this mass was challenging. Excision of this mass was done using an abdominoperineal approach. Histologically, the polypoid lesion was composed of endocervical epithelium with interlacing fascicles and bundles of tumor cells intermixed with endocervical glands. Clinicians should be aware of such lesions so that they can decide upon the appropriate course of management.